Sex differences in the pharmacology of itch therapies—a narrative review. (June 2019) - Schmid, Yasmin; Navarini, Alexander; Thomas, Zita-Rose Manjaly; Pfleiderer, Bettina; Krähenbühl, Stephan; Mueller, Simon M
Abstract : Background: Chronic itch is the most common skin-related condition, associated with a high psychosocial and economic burden. In recent years, increasing evidence of sex differences in the perception, clinical presentation and treatment requirements of itch points towards potential benefits when using sex-adapted therapies. It is well-known that body composition, absorption, metabolism, elimination and adverse drug reactions (ADRs) differ between sexes, but only little is known about the impact of sex in the pharmacology of itch treatments, which could help to rationalise sex-adapted treatment strategies. Aim: To evaluate and review sex effects in the pharmacokinetics and /-dynamics of drugs used to treat itch. Methods: In this narrative review we performed a PubMed and MEDLINE (Ovid) search using the terms (itch OR pruritus) AND (gender OR sex) AND (drug OR medication OR pharmacokinetics OR pharmacodynamics). Additional searches were performed for the topical and systemic drugs recommended by the European Guideline on Chronic Pruritus. Results: We found numerous reports with variable levels of evidence of sex effects with respect to the pharmacokinetics and/or pharmacodynamics of 14 drug classes used for the treatment of itch, including a total of 19 systemic and 3 topical drugs. Women seem to present higher plasma levels of several drugs used in itch treatment, including tri- and tetracyclic antidepressants (e.g. doxepin, amitriptyline, mirtazapine), serotonin reuptake inhibitors (e.g. paroxetine, sertraline, fluoxetine), immunosuppressive drugs (e.g. cyclosporine, mycophenolate mofetil), serotonin receptor antagonists (e.g. ondansetron) and betablockers (e.g. propranolol). Adverse drug reactions (ADRs) were generally more common in women. Being female was reported to be an independent risk factor for QTc-prolongation associated with antihistamines and tetracyclic antidepressants. Additionally, women seem to be more prone to sedative effects of antihistamines, and to suffer from a higher frequency as well as severity of side effects with systemic calcineurin inhibitors, opioid agonists, and opioid antagonists. Women were also sensitised more often to topically applied drugs. Of note, apart from only one experimental study with capsaicin, none of these reports were designed specifically to assess the effect of sex (and gender) in the treatment of itch. Discussion/conclusion: Our review supports previous reports that sex is of importance in the pharmacokinetics and /-dynamics of several drugs used to treat itch although those drugs were mostly evaluated for non-itch indications. However, the results are limited by methodological limitations evident in most studies such as underrepresentation of women in clinical trials. This emphasises the need to study the impact of sex (and gender) in future itch trials to yield better outcomes and prevent ADRs in both sexes.